Spectroscopic interpretation of silver ion complexation with propylene in silver polymer electrolytes - Kim, JH; Min, BR; Kim, CK; Won, J; Kang, YS (AMER CHEMICAL SOC, 2002)
Propylene solubility is almost 2-fold higher in 1:1 poly(2-ethyl-2-oxazoline) (POZ):AgBF4 or poly(vinyl pyrrolidone) (PVP):AgBF4 than in 1: 1 POZ:AgCF3SO3 or 1:1 PVP:AgCF3SO3, according to our previous work. It is confirmed in this paper that the C=C stretching band of propylene coordinated with silver cations in 1: 1 PVP:AgBF4 is about 2-fold more intense than that in 1: 1 PVP:AgCF3SO3. This difference in solubility is investigated here in terms of the differences in the interactions of silver cations with the different anions of the dissolved salts and hence with the carbonyl oxygen atoms of POZ. The strength of interaction between silver cations and carbonyl oxygen, as characterized by the band shift of the complexed C=O bands, arises in the order AgBF4 > AgCF3SO3 > AgNO3, whereas the interaction between the cation and anion, as determined by Raman spectroscopy of ion pairing behavior, shows the order AgBF4 < AgCF3SO3 < AgNO3. addition, these measured differences between the ionic interactions are in agreement with theoretical ab initio calculations of the complexation and bond dissociation energies. It is concluded that AgBF4 polymer electrolytes, with their strong silver cation/carbonyl oxygen and weak, silver cation/anion interactions, exhibit more favorable silver cation complexation of propylene molecules, resulting in higher propylene solubility. Interestingly, we also found that when propylene is introduced into silver polymer electrolytes propylene molecules compete with carbonyl oxygen for coordination with silver cations.
Keywords: FACILITATED OLEFIN TRANSPORT; POLY(ETHYLENE OXIDE); DENSITY; SALTS; MEMBRANES; LICLO4